2016
DOI: 10.1021/acs.jafc.6b00838
|View full text |Cite
|
Sign up to set email alerts
|

Novel Effects of Nanoparticulate Delivery of Zinc on Growth, Productivity, and Zinc Biofortification in Maize (Zea mays L.)

Abstract: In the present investigation, nanoscale zinc oxide particulates (ZnO-nanoparticulates) were prepared using a modified oxalate decomposition method. Prepared ZnO-nanoparticulates (mean size = 25 nm) were characterized using techniques such as transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR), and zeta potential analyzer. Different concentrations (50, 100, 200, 400, 600, 800, 1000, 1500, and 2000 ppm) of ZnO-nanoparticulates were examined to reveal their effects on maize cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
115
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(129 citation statements)
references
References 40 publications
11
115
2
1
Order By: Relevance
“…The important finding that a lower rate of Zn from ZnO-NPs increased grain yield similarly to higher rates from bulk ZnO highlights the value of nano-scale fertilizers as a tool for reducing the rate of fertilizer input in agriculture, while still maintaining equivalent or even increased yields, compared to bulk-scale fertilizers. Along these lines, Subbaiah et al (2016) demonstrated that maize yield could be increased to greater extents by ZnO-NPs at doses 60-98% lower than the bulk Znsulfate dose. However, unlike our study, the Zn rates evaluated by Subbaiah et al (2016) were already high, 50-2,000 mg/L, and the application route was foliar, rather than through the soil.…”
Section: Discussionmentioning
confidence: 93%
“…The important finding that a lower rate of Zn from ZnO-NPs increased grain yield similarly to higher rates from bulk ZnO highlights the value of nano-scale fertilizers as a tool for reducing the rate of fertilizer input in agriculture, while still maintaining equivalent or even increased yields, compared to bulk-scale fertilizers. Along these lines, Subbaiah et al (2016) demonstrated that maize yield could be increased to greater extents by ZnO-NPs at doses 60-98% lower than the bulk Znsulfate dose. However, unlike our study, the Zn rates evaluated by Subbaiah et al (2016) were already high, 50-2,000 mg/L, and the application route was foliar, rather than through the soil.…”
Section: Discussionmentioning
confidence: 93%
“…In potato, long-term field trials showed that the addition of K 2 O 3 Si increased the potato yield by 12.3% [102]. In the case of zinc, application of 1500 ppm of nano-ZnO on corn plants enhanced the yield by 42% as compared to control plants [103]. In addition, the yield of field-grown cucumber plants was increased by 36% using 5 mg kg −1 nano-ZnO [104].…”
Section: Impacts Of Soil Salinity On Chemical Compositions Of Potato mentioning
confidence: 99%
“…The zinc is a necessary micronutrient in regulating various metabolic pathways in plants [29]. The grain yield in nano-ZnO-treated (400 mg L −1 ) maize was 42% and 15% higher than that in the control and ZnSO 4 treated maize [30]. However, the physiochemical mechanisms of nano-ZnO-induced drought tolerance in maize remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%